Attachment to God, Tenure, Race, and Participation in Congregational Life - Kent, Blake Victor; Henderson, W. Matthew (2017)
The vitality of religious congregations is dependent on how effectively they attract congregants and mobilize participation, and people are more likely to participate when they share similar characteristics with other congregants. This study suggests attachment to God is a fundamental behavioral and intrapersonal characteristic which distinguishes participants from one another, contributing to varying levels of participation in congregational and religious life beyond service attendance. Using a national sample, we test several hypotheses related to this theoretical claim. Findings suggest that: (1) secure attachment to God is positively associated with congregational participation, (2) anxious and avoidant attachment are negatively associated with participation, (3) these relationships are moderated by length of time attending a particular congregation, and (4) secure attachment is associated with higher levels of participation in congregational life for blacks than it is for whites. By demonstrating a link between attachment to God and participation in congregational and religious life, this study affirms that intrapersonal characteristics structure the dynamics of religious congregations.
Keywords: Attachment Theory; attachment to God; Organizations; Race; Religion